Akhlak Berbicara Dalam Al - Qur’an - Zulbadri Zulbadri (Fikiran Masyarakat, 2016)
Praiseworthy morals when speaking in accordance with the other party, morals using the correct word in Al - Quran such as talking to parents who are very worthy of glorified, wise words to the orphans, a close relative family, and allusions to the widow who would groom, words to a despotic ruler, and the words to the poor who need a helping hand and compassion of the Muslims who have the advantage.